Divergence before and after the isolation of islands: Phylogeography of the Bradybaena land snails on the Ryukyu Islands of Japan. (21st April 2019) - Hirano, Takahiro; Kameda, Yuichi; Saito, Takumi; Chiba, Satoshi
Abstract: Aim: Vicariance events have been proposed as a major source of lineage divergence on continental islands, whereas dispersal events followed by isolation have been proposed as the major cause on oceanic islands. However, organisms on continental islands may include taxa with characteristics similar to those on oceanic islands. Lineage divergence unassociated with the geological events that separated islands may also have occurred. This study addresses these possibilities through morphological and molecular phylogeographic analyses of land snails ( Bradybaena ) on continental islands. Location: Samples were mainly collected on the Ryukyu and Izu Islands in Japan. Methods: Molecular phylogenetic analyses using mtDNA (16S rRNA+ COI ) and nDNA (18S rRNA+ITS1+5.8S rRNA+ITS2+28S rRNA) were conducted for 225 individuals comprising B. circulus, B. phaeogramma and four of its subspecies endemic to the Ryukyu Islands. Shell and genital morphologies were also examined using qualitative and statistical methods. Results: The Bradybaena populations examined were phylogenetically classified into six major clades whose divergence occurred during either Miocene‐Pliocene or Pliocene‐Pleistocene. Although phylogeographic patterns estimated on the basis of the 16S rRNA gene support the vicariance hypothesis for the origin of the major clades of Bradybaena, the phylogeographic patterns estimated by COI showed that these major clades resulted from diversification before the archipelagos separated from the continent. Both of these phylogeographic patterns suggest that genetic divergence occurred by dispersal from the southern to northern islands after divergence of major clades. The inferred phylogenies document parallel morphological evolution, yielding phylogenetic, morphological and taxonomic incongruences that created mosaic geographical patterns in the distribution of nominal taxa. Main conclusions: Lineage diversification in endemic species on continental islands can occur before archipelago separation or subsequently via dispersal, as is seen in species on oceanic islands. Mechanisms other than vicariance should also be considered when estimating processes that created geographical patterns of genetic variations on continental islands.